2016
DOI: 10.1016/j.jalz.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic proteins predict cognitive decline in Alzheimer's disease and Lewy body dementia

Abstract: METHODS: 129 post-mortem human brain samples were analyzed in brain regional specific manner exploring their associations with morphological changes and cognitive decline.RESULTS: We have observed robust changes reflecting synaptic dysfunction in all studied dementia groups. There were significant associations between the rate of cognitive decline and decreased levels of Rab3 in DLB in the inferior parietal lobe and SNAP25 in AD in the prefrontal cortex. Of particular note, synaptic proteins significantly disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 46 publications
5
113
0
2
Order By: Relevance
“…Of note, several other proteins implicated in PD — in particular, PINK1, Parkin, leucine-rich repeat serine/threonine-protein kinase 2 (LRRK2) and DJ1 — are also involved in synaptic regulation. We have found that reduced neocortical levels of ZnT3, a marker of synaptic plasticity, and two key synaptic proteins, neurogranin and SNAP25 (REFS 31,32), are associated with cognition in PD. These findings suggest that cortical synaptic changes lead to cognitive decline in PD, consistent with imaging findings (see below), and preliminary work indicates that synaptic changes are also reflected in the cerebrospinal fluid (CSF).…”
Section: Mechanismsmentioning
confidence: 99%
“…Of note, several other proteins implicated in PD — in particular, PINK1, Parkin, leucine-rich repeat serine/threonine-protein kinase 2 (LRRK2) and DJ1 — are also involved in synaptic regulation. We have found that reduced neocortical levels of ZnT3, a marker of synaptic plasticity, and two key synaptic proteins, neurogranin and SNAP25 (REFS 31,32), are associated with cognition in PD. These findings suggest that cortical synaptic changes lead to cognitive decline in PD, consistent with imaging findings (see below), and preliminary work indicates that synaptic changes are also reflected in the cerebrospinal fluid (CSF).…”
Section: Mechanismsmentioning
confidence: 99%
“…Several studies associate this hypometabolism with cognitive impairment, suggesting that hypometabolism in PD primarily reflects cognitive deterioration 27, 28. Though a very recent postmortem study suggests that loss of synaptic markers predicts cognitive decline in Lewy body diseases,29 to the best of our knowledge, no direct links have been established between reduced glucose metabolism in PD and independent synaptic markers.…”
Section: Introductionmentioning
confidence: 99%
“…In the brains of patients with DLB and PDD, most α‐synuclein aggregates are located in the presynaptic terminals and cause synaptic dysfunction via significant reduction of pre‐ and postsynaptic proteins, such as synaptophysin and drebrin . To quantitatively evaluate the effects of abnormal α‐synuclein accumulation on synaptic proteins in the frontal cortex and hippocampus, we assessed synaptophysin and synapsin I levels as presynaptic markers and drebrin and PSD‐95 levels as postsynaptic markers using capillary western blot.…”
Section: Resultsmentioning
confidence: 99%